Herpetofauna Diversity based on Microhabitat Characteristics at Two Altitudinal Levels in Bukit Barisan Selatan National Park - Baswedann, Balya Baried; Adifitri, Risa Dita; Fitrih, Ghesya Adinda Yulia; Rizdallah, Muhammad Arafi; Djahabiyyah, Putri Atiqoh; Mefida, Lidya Ika; Arizki, Dyah Ayu; Master, Jani (Biospecies, 2024)
Bukit Barisan Selatan National Park is a strategic conservation area. The existence of herpetofauna, which includes reptiles and amphibians, is an integral part of the ecosystem of this national park. Research on herpetofauna in TNBBS is relevant considering the potential threats to biodiversity due to climate change, habitat destruction, and human activities that affect the habitat conditions of these fauna groups. Based on this, this research is intended to explore the diversity of herpetofauna as an environmental bioindicator based on microhabitat characteristics at two altitude levels, namely highlands (Resort Sukaraja Atas) and lowlands (Way Canguk Research Station), Bukit Barisan Selatan National Park (TNBBS). This study was conducted in July 2023 in two locations, namely Sukaraja Atas Resort representing the highlands and Way Canguk Research Station representing the lowlands. Sampling used line transect and VES (Virtual Encounter Survey) methods. The results showed that both locations, Way Canguk Research Station and Upper Sukaraja Resort, had moderate amphibian and reptile species diversity (2.7). Although diversity and evenness indices showed similarities between the two sites, Upper Sukaraja Resort stood out with a higher species richness value (5.7) compared to Way Canguk Research Station (4.9).